2018
DOI: 10.4236/oje.2018.83014
|View full text |Cite
|
Sign up to set email alerts
|

Tree Biomass Estimation in Central African Forests Using Allometric Models

Abstract: Quantifying the tropical forests' carbon stocks is presently an important component in the implementation of the emerging carbon credit market mechanisms. This calls for appropriate allometric equations predicting biomass which currently are scarce. In this study, we aimed to estimate above-and below-ground biomass and carbon stocks of trees, and to identify the variation in diameter-height allometry of Ipendja mixed terra firme lowland tropical forest's trees. The study area is located at Ipendja forest manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…The maximum AGC value recorded in a single plot in the current study was 916 Mg C ha −1 , which is approximately threefold higher than previous published values for Congo forests and close to the world's highest known AGC stock, 1053 Mg C ha −1 , found in Australian temperate moist Eucalyptus regnans forests (Keith et al, 2009). Overall, carbon stocks for terra firme associations at Mayoko, except for A9 and A12, exceeded the mean AGC value reported for RoC's Likouala and Pool Department (Bocko et al, 2017; Ekoungoulou et al, 2015, 2018) as well as at Monts Birougou National Park, Gabon (Gautam & Pietsch, 2012). Such high carbon values were associated with a high mean basal area (47.73 m 2 ) which was also higher than published values for tropical forests (Chave et al, 2003; Djuikouo et al, 2010; Feldpausch et al, 2011; Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The maximum AGC value recorded in a single plot in the current study was 916 Mg C ha −1 , which is approximately threefold higher than previous published values for Congo forests and close to the world's highest known AGC stock, 1053 Mg C ha −1 , found in Australian temperate moist Eucalyptus regnans forests (Keith et al, 2009). Overall, carbon stocks for terra firme associations at Mayoko, except for A9 and A12, exceeded the mean AGC value reported for RoC's Likouala and Pool Department (Bocko et al, 2017; Ekoungoulou et al, 2015, 2018) as well as at Monts Birougou National Park, Gabon (Gautam & Pietsch, 2012). Such high carbon values were associated with a high mean basal area (47.73 m 2 ) which was also higher than published values for tropical forests (Chave et al, 2003; Djuikouo et al, 2010; Feldpausch et al, 2011; Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 63%
“…A comparison of plots with and without the ≥10-15 cm cohort, indicated that this size class constituted 1-2.5% of the mean AGC in the three associations compared. Ekoungoulou et al, 2015Ekoungoulou et al, , 2018 as well as at Monts Birougou National Park, Gabon (Gautam & Pietsch, 2012). Such high carbon values were associated with a high mean basal area (47.73 m 2 ) which was also higher than published values for tropical forests (Chave et al, 2003;Djuikouo et al, 2010;Feldpausch et al, 2011;Lewis et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…To determine the biomass and, hence, the amounts of carbon stored above and below ground in trees, non-destructive allometric approach was used. Siteor species-specific allometric equations are preferred because they yield more unavailable, however, general ones are often substituted (Ekoungoulou et al, 2018).…”
Section: Tree Species Inventory and Carbon Storage Potentialmentioning
confidence: 99%
“…Aboveground biomass (AGB) plays a significant role in the study of the climate change in the global terrestrial biota. Ekoungoulou et al (2018) reported that as atmospheric CO 2 concentrate and its consequence on global climate change continues to increase; quantification of aboveground biomass (AGB) of tree ecosystems is needed to provide information on the carbon budgets. The estimation of carbon stored in trees may offer noteworthy evidence on carbon flux owing to water circulation, which may eventually permit assessment of the carbon cycle (Pinzón et al, 2020).…”
Section: Introductionmentioning
confidence: 99%